Ni-BASED ALLOY, CONTINUOUS CASTING MOLD COATED WITH Ni-BASED ALLOY, AND METHOD FOR PRODUCING MOLD

A self-melted Ni base alloy with tailored thermal expansion and wear resistance addresses peeling and corrosion issues in continuous casting molds, ensuring durable and efficient operation.

JP2025011988APending Publication Date: 2025-01-24FUKUDA METAL FOIL & POWDER CO LTD +1

Patent Information

Application Number
JP2023114482
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing coatings for continuous casting molds, such as melting films and plating layers, face issues with peeling due to mismatched thermal expansion coefficients and poor wear resistance, leading to corrosion and reduced productivity.

Method used

Development of a self-melted Ni base alloy with a linear expansion coefficient matching copper or copper alloys, combined with high wear resistance and suitable for re-dissolving processing, formulated with specific compositions of Mn, B, Si, Cu, Mo, Cr, Fe, and Co to ensure adhesion and durability.

Benefits of technology

The Ni base alloy provides a coating that remains adherent to the copper substrate through re-melting processes, offering enhanced wear resistance and minimizing dimensional changes, thus improving the longevity and performance of continuous casting molds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025011988000003
    Figure 2025011988000003
  • Figure 2025011988000004
    Figure 2025011988000004
  • Figure 2025011988000005
    Figure 2025011988000005
Patent Text Reader

Abstract

To provide a Ni-based alloy with a linear expansion coefficient comparable to that of copper or copper alloy, a continuous casting mold with its inner surface coated with the Ni-based alloy, and a method for producing the same.SOLUTION: A Ni-based alloy comprises Mn of 15.0-35.0 mass%, B of 0.2-3.5 mass%, and Si of 0-4.5 mass%; optionally, at least one selected from the group consisting of Mo, Cu, and Cr, with the total amount of Mo, Cu, and Cr being 0-20.0 mass%; optionally, at least one selected from the group consisting of Fe and Co, with the total amount of Fe and Co being 0-10.0 mass%; and the balance being Ni and unavoidable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Ni-base alloy, and in particular to a Ni-base alloy suitable for coating the inner surface (surface in contact with molten steel) of a continuous casting mold used to produce cast slabs. The present invention also relates to a continuous casting mold the inner surface of which is coated with the Ni-base alloy, and a method for producing the same. [Background technology]

[0002] A slab is obtained by pouring molten steel into a continuous casting mold, followed by cooling and solidification. At that time, the inner surface of the mold (made of copper or copper alloy) comes into contact with the molten steel or the solidified slab via a lubricant, so the mold surface is easily worn. In addition, water used for cooling the lower part of the mold reacts with the lubricant components to generate corrosive gases and corrosive solutions, which causes a problem of corrosion of the mold surface. For this reason, the inner surface of the mold is coated with a thermal spray coating or a plating layer, as shown in Patent Documents 1 to 3. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-031867 A [Patent Document 2] JP 2002-086248 A [Patent Document 3] Japanese Patent Application Publication No. 03-071955

[0004] In the case of thermal spray coating, a self-fluxing alloy is sprayed onto a substrate to form a coating, which is then subjected to a remelting process (fusing) to improve adhesion to the substrate and to densify the coating. However, if there is a large difference between the linear expansion coefficient of the alloy used as the thermal spray material and the linear expansion coefficient of the substrate, copper or copper alloy, during the heating process of the remelting process, the thermal spray coating will follow the copper or copper alloy, which has a larger linear expansion coefficient, while during the cooling process, the copper or copper alloy will follow the thermal spray coating, which has a smaller linear expansion coefficient. This can lead to problems such as the thermal spray coating being easily peeled off, or, if the thermal spray coating does not peel off, the substrate (copper or copper alloy member) undergoing a large dimensional change.

[0005] Furthermore, since a plated layer has lower abrasion resistance than a thermal spray coating, the plated layer must be made thicker, which results in problems such as longer plating time, poor productivity, and the need for waste liquid treatment. Summary of the Invention [Problem to be solved by the invention]

[0006] Therefore, there is a need to develop a self-fluxing alloy that can be used in thermal spraying methods that do not generate waste liquid during coating processing and have a low environmental impact, and that has higher abrasion resistance than plating and a linear expansion coefficient close to that of the base material, copper or copper alloy. [Means for solving the problem]

[0007] In the present invention, the mold material is copper or a copper alloy (generally having a linear expansion coefficient of 16.5 to 18.5 × 10 at 30 to 300 ° C. -6 In examining the composition of a Ni-based alloy with a linear expansion coefficient close to that of the alloy of the present invention (100 / °C), the following target values ​​were set, and the aim was to satisfy all of them. (1) Linear expansion coefficient: 15.0 to 19.0 x 10 at 30 to 300°C -6 / ℃ range (2) Abrasion resistance: Rockwell hardness of 25HRC or more (3) Remelting process possible: solidus temperature is 1050℃ or less

[0008] The Ni-based alloy (particularly, thermal spray powder) of the present invention that satisfies the above objectives (1) to (3) has the following composition. [1] containing 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; optionally containing at least one selected from the group consisting of Mo, Cu, and Cr, and the total amount of Mo, Cu, and Cr is 0 to 20.0 mass; optionally containing at least one selected from the group consisting of Fe and Co, the total amount of Fe and Co being 0 to 10.0 mass%; The balance is Ni and unavoidable impurities. A Ni-based alloy characterized by: [2] Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; The Ni-based alloy according to [1], wherein the balance is Ni and unavoidable impurities. [3] Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Further, at least one selected from the group consisting of Mo, Cu, and Cr, The Ni-based alloy according to [1], wherein the balance is Ni and unavoidable impurities. [4] Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Further, at least one selected from the group consisting of Fe and Co is contained, The Ni-based alloy according to [1], wherein the balance is Ni and unavoidable impurities. [5] Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Further, at least one selected from the group consisting of Mo, Cu, and Cr, and at least one selected from the group consisting of Fe and Co, The Ni-based alloy according to [1], wherein the balance is Ni and unavoidable impurities. [6] The linear expansion coefficient of the cast piece at 30 to 300°C is 15.0 to 19.0 × 10 -6 / °C.

[0009] The present invention also provides a thermal spray powder made of the Ni-based alloy according to any one of [1] to [6].

[0010] The present invention also provides a continuous casting mold, characterized in that the copper or copper alloy surface (surface in contact with molten steel) on the inside of the mold is coated with the Ni-based alloy according to any one of [1] to [6].

[0011] The present invention also provides a method for producing a continuous casting mold having an inner surface coated with a Ni-based alloy, the method comprising the steps of: spraying a thermal spray powder made of the Ni-based alloy according to any one of [1] to [6] onto a copper or copper alloy surface that will become the inner surface of the mold to form a coating layer; After forming the coating layer, a remelting process is performed at a temperature in the range of 950 to 1100°C to form a diffusion layer at the boundary between the copper or copper alloy and the coating layer. The present invention is characterized by comprising: Effect of the Invention

[0012] The Ni-based alloy of the present invention has a linear expansion coefficient close to that of copper or a copper alloy and is wear-resistant, and is therefore suitable for surface-hardening coating of copper or copper alloy substrates (particularly, copper or copper alloy members of a continuous casting mold) having a large linear expansion coefficient. The coating layer made of the Ni-based alloy of the present invention has the effect that the coating layer is unlikely to peel off from the copper or copper alloy substrate even when a remelting process is performed, or that the dimensional change of the copper or copper alloy substrate can be suppressed. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic diagram showing components constituting a continuous casting mold. [Diagram 2]FIG. 2 shows a schematic diagram of a thermal sprayed film (coating layer) made of a Ni-based alloy formed on the surface of a copper or copper alloy substrate. [Diagram 3] FIG. 3 shows a cross-sectional structure image (before surface processing) of a copper alloy substrate after the Ni-based alloy powder of the present invention is sprayed onto the substrate to form a thermal spray coating (coating layer) made of a Ni-based alloy, followed by remelting treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The reasons for limiting the components of the Ni-based alloy of the present invention are described below.

[0015] Mn has the effect of increasing the linear expansion coefficient when added to Ni. However, if the Mn content is less than 15.0%, the linear expansion coefficient of the cast piece at 30 to 300°C is 15.0×10 -6 / ℃, and when Mn exceeds 35.0 mass%, the linear expansion coefficient of the cast piece at 30 to 300℃ tends to be smaller than 19.0×10 -6 / ° C. Therefore, the Mn content is limited to the range of 15.0 to 35.0 mass %. A more preferable range for the Mn content is 15.0 to 25.0 mass %.

[0016] B lowers the solidus temperature and contributes to improving hardness, thereby improving wear resistance. However, if B is less than 0.2 mass%, the solidus temperature is not lowered sufficiently, and remelting treatment cannot be performed at a temperature range of 950 to 1100°C (preferably, solidus temperature +20 to 200°C) after the thermal spray coating is formed, and a dense coating tends not to be obtained. If B exceeds 3.5 mass%, the amount of intermetallic compounds increases, the amount of solid solution decreases, the coating becomes brittle, and the crack resistance of the coating tends to decrease. Therefore, B is limited to the range of 0.2 to 3.5 mass%. A more preferable amount of B is 0.2 to 2.5 mass%, at which the Rockwell hardness is 50HRC or less.

[0017] The Ni-based alloy of the present invention may not contain Si, or may contain Si. Si can lower the solidus temperature and contribute to improving hardness, thereby improving wear resistance. However, if the Si content exceeds 4.5 mass%, the amount of solid solution decreases due to an increase in the amount of intermetallic compounds, making the coating brittle and tending to reduce the crack resistance of the coating. Therefore, the Si content is limited to a range of 0 to 4.5 mass%. When the melting temperature is to be lowered, the Si content is more preferably 1.5 mass% or more, and more preferably the Si content is 1.5 mass% or more and the B content is 1.0 mass% or more.

[0018] The Ni-based alloy of the present invention may not contain Cu, Mo, and Cr, or may contain at least one selected from them (i.e., it may contain only one selected from Cu, Mo, and Cr, may contain any two selected from Cu, Mo, and Cr, or may contain all of Cu, Mo, and Cr). Cu, Mo, and Cr contribute to improving corrosion resistance, and Mo and Cr contribute to improving wear resistance by forming an intermetallic compound. However, if the total amount of them exceeds 20.0 mass%, the amount of solid solution decreases due to the increase in the amount of intermetallic compounds, and the intermetallic compounds become coarse, making the film brittle and tending to reduce the crack resistance of the film. Therefore, the total amount of Cu, Mo, and Cr is limited to a range of 20.0 mass% or less. From the viewpoint of imparting corrosion resistance, the total amount of Cu and Mo is preferably 3.0 mass% or more.

[0019] The Ni-based alloy of the present invention may not contain Fe and Co, or may contain either one of Fe and Co, or may contain both Fe and Co. However, when the amount of Fe and / or Co in the Ni-based alloy is large, the solid solubility limit is narrowed, the amount of intermetallic compounds formed increases, the coating becomes brittle, and the crack resistance of the coating tends to decrease. Fe also tends to cause a decrease in corrosion resistance. Therefore, the total amount of Fe and Co is limited to a range of 10.0 mass% or less. The total amount of Fe and Co is more preferably 8.0 mass% or less, and further preferably 5.0 mass% or less.

[0020] In the Ni-based alloy of the present invention, the balance other than the above components (Mn, B, Si, Cu, Mo, Cr, Fe, Co) consists of Ni and inevitable impurities. The Ni content in the Ni-based alloy is preferably 50.0 mass% or more, and particularly preferably in the range of 50.0 to 75.0 mass%. In this specification, inevitable impurities refer to impurities that are not intentionally added but are inevitably mixed in during the manufacturing process of each raw material. The total amount of inevitable impurities is usually 0.4 mass% or less, which is not enough to affect the action of the present invention. Since the amount of inevitable impurities is preferably small, the total amount is more preferably 0.3 mass% or less, 0.2 mass% or less, or 0.1 mass% or less, and may be 0 mass%.

[0021] The Ni-based alloy of the present invention has a linear expansion coefficient of 15.0 to 19.0 × 10 at 30 to 300 ° C. -6 / °C. The linear expansion coefficient of the cast piece can be measured by the method described in the Examples. The Ni-based alloy having a linear expansion coefficient within the above range is suitable for spraying onto a copper or copper alloy substrate having a large linear expansion coefficient to form a thermal spray coating (coating layer), and the obtained thermal spray coating is not easily peeled off from the substrate during remelting treatment, or the dimensional change of the substrate can be suppressed. In addition, since the Ni-based alloy of the present invention has a linear expansion coefficient close to that of stainless steel (e.g., austenitic stainless steel), it is also useful as a coating material for hardening the surface of a stainless steel substrate, and can exert the same effect as when used for coating a copper or copper alloy substrate.

[0022] The Ni-based alloy of the present invention is suitable for use as a powder for thermal spraying. For example, the Ni-based alloy powder produced by the atomization method can be adjusted to a particle size suitable for the intended thermal spraying method, and can be used as a powder for thermal spraying methods such as flame spraying, plasma spraying (e.g., atmospheric plasma spraying), and high-velocity flame spraying. The atomization method is a method in which molten metal is scattered and the droplets are solidified to powderize, and includes water atomization, gas atomization, and vacuum atomization. For example, a base metal in which Ni and added components Mn, B, Si, Cu, Mo, Cr, Fe, and Co are adjusted and mixed to a predetermined mass%, is heated and melted in a crucible in a melting furnace to form a liquid alloy, which is then powdered by the atomization method, and the obtained atomized powder is adjusted to a predetermined particle size, thereby obtaining a powder suitable for thermal spraying methods (e.g., flame spraying, high-velocity flame spraying, and plasma spraying).

[0023] When used as a thermal spray powder, the particle size range of the Ni-based alloy powder is preferably adjusted to 10 to 45 μm, 20 to 53 μm, 20 to 63 μm, 45 to 75 μm, 45 to 106 μm, 45 to 150 μm, 75 to 150 μm, etc. (for example, using a vibrating sieve or an air classifier, the Ni-based alloy powder is adjusted so that 80 to 100% by volume or 80 to 100% by mass, preferably 90 to 100% by volume or 90 to 100% by mass is within the above particle size range). In the case of fine powders such as 10 to 45 μm, 20 to 53 μm, and 20 to 63 μm, it is preferable that the powder contains 80 volume % or more of powder within the desired particle size range in particle size distribution measurement using the laser diffraction / scattering method specified in JIS Z 8825, and in the case of coarse powders such as 45 to 75 μm, 45 to 106 μm, 45 to 150 μm, and 75 to 150 μm, it is preferable that the powder contains 80 mass % or more of powder within the desired particle size range in particle size distribution measurement using the metal powder-dry sieving method specified in JIS Z 2510.

[0024] A thermal spray coating (coating layer) can be formed by spraying a thermal spray powder made of a Ni-based alloy on the surface of a copper or copper alloy substrate using a thermal spraying method such as plasma spraying, flame spraying, or high-velocity flame spraying. In addition, after forming the thermal spray coating, it is preferable to heat treat (remelt treatment) the thermal spray coating. This heat treatment can be performed, for example, in a heating furnace, and for example, the thermal spray coating is heated for about 10 to 30 minutes in an oxygen-free atmosphere or in an inert atmosphere filled with nitrogen gas. The temperature is preferably 950 to 1100°C, and more preferably in the range of the solidus temperature of the Ni-based alloy +20 to 200°C. This causes diffusion to start near the interface between the thermal spray coating and the copper or copper alloy surface, improving adhesion. The Ni-based alloy of the present invention has a linear expansion coefficient close to that of copper or copper alloy, so that the coating layer is less likely to peel off from the substrate and the substrate is less likely to deform during the heating step and the subsequent cooling step in the remelt treatment. Furthermore, the coating layer made of the Ni-based alloy of the present invention has high wear resistance, and therefore can strengthen the mold surface and prevent wear.

[0025] The Ni-based alloy of the present invention is particularly suitable as a coating material for a continuous casting mold. A continuous casting mold usually has two long side mold members and two short side mold members that are sandwiched between them and can move. When molten steel is poured from above into a space (inside the mold) surrounded by four mold members, the molten steel part in contact with the mold solidifies to form a solidified shell (cast piece), which is then pulled out below the mold, and the cast piece is continuously produced. FIG. 1 shows one long side mold member and one short side mold member. The long side mold member 1 and the short side mold member 5 each have a copper plate (3 or 7) made of copper or a copper alloy, and a back plate (2 or 6) that contacts the back surface of the copper plate and cools the copper plate. A coating layer (4 or 8) is formed on the surface of the copper plate (the surface that contacts molten steel), and this is formed by spraying the Ni-based alloy powder of the present invention (e.g., atomized powder) onto the copper plate. 、It is a thermal spray coating (coating layer) formed by performing a remelting process. The coating layer is preferably formed on at least a part of the surface inside the mold that contacts the molten steel, preferably on the entire surface that contacts the molten steel. The continuous casting mold according to the present invention includes not only a mold having a rectangular hollow portion as described above, but also molds of other shapes (for example, tubular type). The final thickness of the coating layer after surface processing such as grinding is preferably about 0.1 to 1.5 mm. As shown in FIG. 2, the thickness of the coating layer 10 (4 or 8) on the copper plate 9 (3 or 7) does not need to be uniform, and it is preferable that the coating layer becomes thicker continuously from the top to the bottom of the copper plate. For example, the thickness of the coating layer is preferably 0.1 mm to 0.5 mm at the top end of the copper plate (i.e., the top of the mold) and 0.5 to 1.5 mm at the bottom end of the copper plate (i.e., the bottom of the mold). EXAMPLES

[0026] [Characteristics evaluation] Ni-based alloys of the examples and comparative examples were produced by melting metals that were adjusted and mixed to have the alloy compositions shown in Tables 1 and 2. Next, the linear expansion coefficient, Rockwell hardness (an index of wear resistance), and melting temperature range were evaluated by the methods described below.

[0027] (1) Linear expansion coefficient 100 g of ingots containing each alloy composition were heated to approximately 1650°C in an argon stream using an electric furnace, and the molten metal was drawn up using a glass tube casting rod with an inner diameter of 5 mm and a dropper to produce a round rod with a diameter of 5 mm (glass tube cast piece). This cast piece was cut to a length of 15 mm, and the cut surfaces (both sides) were adjusted to be parallel and have a surface roughness using a surface grinder (abrasive grain #80) to produce a φ5×15 mm test piece. The linear expansion coefficient was then measured in a nitrogen stream from 30 to 300°C using a thermomechanical analyzer (TMA) manufactured by Rigaku Corporation. The linear expansion coefficient of the cast piece at 30 to 300°C was 15.0 to 19.0×10 -6 / ℃ range was considered to be acceptable.

[0028] (2) Rockwell hardness 100g of ingots of each alloy composition were heated to about 1650℃ in an argon gas stream in an electric furnace, melted, and cast in a shell mold. The cast pieces were then machined to about 10×10×20mm, and the parallel surfaces and surface roughness were adjusted using a surface grinder (abrasive grain #80) to prepare test pieces. Rockwell hardness tests were then conducted in accordance with JIS Z 2245:2005. Hardness measurements were performed using the C scale, and a Rockwell hardness of 25 or more was considered to be acceptable as the standard for wear resistance.

[0029] (3) Measurement of solidus temperature 100g of ingots with each alloy composition were heated to about 1650℃ in an argon gas stream in an electric furnace, melted, and then an alumina protective tube containing an R thermocouple was inserted into the molten metal, followed by slow cooling to obtain a time-temperature curve during cooling. The bending point associated with the endothermic reaction that occurs during solidification was read from the time-temperature curve, and the final solidification temperature (solidus temperature) was obtained. A solidus temperature of 1050℃ or less was considered acceptable.

[0030] Table 1 shows examples of Ni-based alloys according to the present invention, and Table 2 shows comparative alloys. In the table, "Bal." for Ni refers to the remainder (balance) obtained by subtracting the mass percentages of the elements other than Ni (Mn, B, Si, Cu, Mo, Cr, Fe, Co, C) listed in the table from 100 mass%.

[0031] [Table 1]

[0032] [Table 2]

[0033] Comparative alloys No. 16 to No. 23 shown in Table 2 failed to satisfy one or more of the targets for linear expansion coefficient, Rockwell hardness, and solidus temperature. Nos. 16 to 18, which contain less than 15.0 mass% Mn, had a linear expansion coefficient of 15.0×10 -6 / °C. No. 17 (SFNi4: NiCrCuMoBSi 69 15 3 3A as specified in JIS H 8303), which contains less than 15.0 mass% Mn, more than 20.0 mass% total Cu, Mo and Cr, and also contains C, showed the lowest linear expansion coefficient. No. 18 failed to achieve the target values ​​for both linear expansion coefficient and Rockwell hardness. No. 19, which contains more than 35.0 mass% Mn, showed a linear expansion coefficient of 19.0 × 10 -6 No. 20, in which B was less than 0.2 mass%, had a Rockwell hardness of less than 25 and a solidus temperature of more than 1050°C. No. 21, in which B was more than 3.5 mass%, and No. 22, in which the total amount of Cu, Mo, and Cr was more than 20.0 mass%, had a linear expansion coefficient of 15.0 × 10 -6 No. 23, which contains more than 4.5 mass% Si and more than 10.0 mass% Co, exhibited a linear expansion coefficient of 19.0 × 10 -6 / °C.

[0034] In contrast, as shown in Table 1, the Ni-based alloys of the present invention, Example Nos. 1 to 15, satisfied all the target values ​​for linear expansion coefficient, Rockwell hardness, and solidus temperature. These Ni-based alloys not only have solidus temperatures suitable for remelting treatment, but also have linear expansion coefficients close to those of copper or copper alloys, so that even if remelting treatment is performed after the formation of the thermal spray coating, the thermal spray coating is unlikely to peel off from the copper or copper alloy substrate, and the dimensional change of the substrate can be suppressed. Furthermore, since they have high Rockwell hardness, they are useful as coating materials with wear resistance.

[0035] [Dimensional change test of substrate] 100 kg of ingots having the compositions of Example No. 11 in Table 1 and Comparative Example No. 17 in Table 2 were heated and melted at about 1650°C in an air atmosphere using a high-frequency melting furnace, powdered by a gas atomization method, and adjusted to a particle size of 20 to 53 μm using a vibrating sieve. The obtained Ni-based alloy powder was used to form a coating layer (thickness: about 1.5 mm) on the surface of a blasted copper alloy substrate (900 x 50 mm, thickness 20 mm, CuCr1Zr described in JIS Z 3234) by a high-velocity flame spraying method. Thereafter, the coated substrate was placed in a vacuum furnace set at 1030°C and heat-treated (remelting treatment), and the dimensional change of the substrate was evaluated.

[0036] The longitudinal dimensional change of the substrate was 0.1 mm in Example No. 11, whereas it was 1.2 mm in Comparative Example No. 17. In addition, the copper alloy member coated in Example No. 11 had a warpage (height of the center of the substrate in the longitudinal direction when the coated substrate was placed on a flat surface) of 3.0 mm, whereas the copper alloy member coated in Comparative Example No. 17 had a warpage of 18.5 mm. These results demonstrate that the copper alloy substrate coated with the Ni-base alloy of the present invention has a small dimensional change even after remelting treatment.

[0037] [Wear resistance test] In the same manner as in the dimensional change test, a coating layer made of the Ni-based alloy of Example No. 11 was formed on a copper alloy substrate, and the wear resistance was measured and compared with that of the Ni plating film.

[0038] Abrasion resistance was measured using a ring-on-disk abrasion tester, where a ring (inner diameter 20 mm x outer diameter 26 mm) was pressed against the coating surface (disk) at a surface pressure of 50 kg / cm. 2 The test was carried out under conditions of a test speed of 30 rpm, a test distance of 78.5 m, and 300°C in air, and the weight loss of the disk (coating layer) was evaluated. The surface roughness of the wear surface was adjusted using #240 waterproof abrasive paper for the disk and #320 waterproof abrasive paper for the ring.

[0039] As a result of the wear resistance test (the greater the weight loss of the disk due to wear, the lower the wear resistance), the weight loss of the Ni plating layer was 150 mg, while the weight loss of the Ni-based alloy coating layer of Example No. 11 was 50 mg, demonstrating that the coating layer made of the Ni-based alloy of the present invention has higher wear resistance than the Ni plating layer.

[0040] [Cross-section observation] A 50x900x20mm copper alloy substrate was coated with Ni-based alloy powder of Example No. 11, the particle size of which was adjusted to 20-53μm, by high-velocity flame spraying to form a coating layer (sprayed film) of about 1.5mm thickness on the copper alloy substrate. The copper alloy substrate was then placed in a vacuum furnace at 1030℃ and remelted, and the cross-sectional structure was observed (Fig. 3).

[0041] As shown in Fig. 3, it was confirmed that the coating layer 12 made of the Ni-based alloy of the present invention has a diffusion layer 13 formed by the remelting treatment at the interface with the substrate 11, and has few pores and oxides. It was also demonstrated that the Ni-based alloy of the present invention can be subjected to thermal spraying and remelting treatment. [Industrial Applicability]

[0042] As described above, the Ni-based alloy of the present invention is useful as a thermal spray powder, and has a linear expansion coefficient close to that of copper or copper alloy members, so that even if the Ni-based alloy coating layer (thermal spray coating) is formed by thermal spraying on a copper or copper alloy member (substrate) and then a remelting process is performed, peeling of the coating layer and dimensional change of the substrate are unlikely to occur. In addition, because of its high hardness, the Ni-based alloy is useful as a coating material for copper or copper alloy members, particularly as a coating material for surface hardening, and is expected to extend the life of the members.

[0043] Furthermore, the Ni-base alloy of the present invention has a linear expansion coefficient close to that of not only copper or copper alloy substrates but also stainless steels, particularly austenitic stainless steels, which have a large linear expansion coefficient, and therefore can be widely used in applications other than coating of continuous casting molds. [Explanation of symbols]

[0044] 1 Long side mold member 2 Long Side Backplate 3 Long side copper plate 4 Coating layer (long side) 5 Short side mold parts 6 Short Side Backplate 7 Short side copper plate 8 Coating layer (short side) 9 Copper plate 10 Thermal spray coating 11 Cross-sectional structure of copper alloy substrate 12 Cross-sectional structure of thermal spray coating 13 Cross-sectional structure of the diffusion layer

Claims

1. Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Optionally, at least one selected from the group consisting of Mo, Cu, and Cr, wherein the total amount of Mo, Cu, and Cr is 0 to 20.0 mass %; Optionally, at least one selected from the group consisting of Fe and Co, wherein the total amount of Fe and Co is 0 to 10.0 mass%; The balance is Ni and unavoidable impurities. A Ni-based alloy characterized by:

2. Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; The Ni-based alloy according to claim 1, wherein the balance is Ni and unavoidable impurities.

3. Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Further, at least one selected from the group consisting of Mo, Cu, and Cr, The Ni-based alloy according to claim 1, wherein the balance is Ni and unavoidable impurities.

4. Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Further, at least one selected from the group consisting of Fe and Co is contained, The Ni-based alloy according to claim 1, wherein the balance is Ni and unavoidable impurities.

5. Contains 15.0 to 35.0 mass% Mn, 0.2 to 3.5 mass% B, and 0 to 4.5 mass% Si; Further, at least one selected from the group consisting of Mo, Cu, and Cr, and at least one selected from the group consisting of Fe and Co, The Ni-based alloy according to claim 1, wherein the balance is Ni and unavoidable impurities.

6. The linear expansion coefficient of the cast piece at 30 to 300°C is 15.0 to 19.0 x 10 -6 The Ni-based alloy according to any one of claims 1 to 5, wherein the range is 0.1 to 1.0 °C.

7. A thermal spray powder comprising the Ni-based alloy according to any one of claims 1 to 5.

8. A continuous casting mold, characterized in that the copper or copper alloy surface on the inside of the mold is coated with the Ni-based alloy according to any one of claims 1 to 5.

9. A method for producing a continuous casting mold having an inner surface coated with a Ni-based alloy, comprising the steps of: A step of spraying the thermal spray powder made of the Ni-based alloy according to any one of claims 1 to 5 onto the copper or copper alloy surface that will be the inside of a mold to form a coating layer; and After forming the coating layer, a remelting process is performed at a temperature in the range of 950 to 1100°C to form a diffusion layer at the interface between the copper or copper alloy and the coating layer. A method for producing a continuous casting mold, comprising:

Citation Information

Patent Citations

  • Mold for continuous casting

    JP1991071955A

  • Die for continuous casting

    JP2002086248A

  • Casting mold for continuous casting

    JP2013031867A

Cited By

  • Powder for crystallizer copper plate coating

    CN121874569A